The Effects of Serum Proteins on Magnesium Alloy Degradation in Vitro. Issue 1 (December 2017) - Johnson, Ian; Jiang, Wensen; Liu, Huinan
Abstract Magnesium (Mg) alloys are promising materials for biodegradable implants, but their clinical translation requires improved control over their degradation rates. Proteins may be a major contributing factor to Mg alloy degradation, but are not yet fully understood. This article reports the effects of fetal bovine serum (FBS), a physiologically relevant mixture of proteins, on Mg and Mg alloy degradation. FBS had little impact on mass loss of pure Mg during immersion degradation, regardless of whether or not a native oxide layer was present on the sample surface. FBS reduced the mass loss of Mg-Yttrium (MgY) alloy with an oxidized surface during immersion degradation, but increased the mass loss for the same alloy with a metallic surface (surface oxides were removed). FBS also influenced the mode of degradation by limiting the depth of pit formation during degradation processes on commercially pure Mg with metallic or oxidized surfaces and on MgY alloy with oxidized surfaces. The results demonstrated that serum proteins had significant interactions with Mg-based biodegradable metals, and these interactions may be modified by alloy composition and processing. Therefore, proteins should be taken into account when designing experiments to assess degradation of Mg-based implants.